Investigação do início de ativação de músculos do tronco durante realização de tarefa motora em homens com e sem dor lombar. - Polato, Danielle (2017)
The present work used surface electromyography to identify the activation times of some trunk muscles during the beginning of the movement of extension of this segment in three distinct angular velocities in order to describe muscular synergism in volunteers with and without chronic low back pain (LBP). The energy patterns of the EMG signals were also investigated by topographic images during a trunk extension-flexion-extension cycle. The study included 18 men equally divided into two groups, with and without LBP, and used isokinetic equipment to control speed and angle of movement. When comparing muscle activation times between groups, the results were statistically significant for the upper rectus abdominis, lower rectus abdominis and external oblique muscles at speeds of 120°/s and 90°/s; And only for the upper rectus abdominis at 60°/s. These results indicate the presence of co-contraction between the flexor and extensor muscles of the trunk during the onset of movement in the DLC group. The topographic images presented for volunteers with chronic low back pain were able to show this behavior. The anticipatory activation to the movement of the transverse abdomen/internal oblique muscle was present in both groups. No asymmetry was found between the sides of the muscles investigated in any of the groups.